Maintenance of temporal synchrony between syrphid flies and floral resources despite differential phenological responses to climate. (29th May 2013) - Iler, Amy M.; Inouye, David W.; Høye, Toke T.; Miller‐Rushing, Abraham J.; Burkle, Laura A.; Johnston, Eleanor B.
Abstract: Variation in species' responses to abiotic phenological cues under climate change may cause changes in temporal overlap among interacting taxa, with potential demographic consequences. Here, we examine associations between the abiotic environment and plant–pollinator phenological synchrony using a long‐term syrphid fly–flowering phenology dataset (1992–2011). Degree‐days above freezing, precipitation, and timing of snow melt were investigated as predictors of phenology. Syrphids generally emerge after flowering onset and end their activity before the end of flowering. Neither flowering nor syrphid phenology has changed significantly over our 20‐year record, consistent with a lack of directional change in climate variables over the same time frame. Instead we document interannual variability in the abiotic environment and phenology. Timing of snow melt was the best predictor of flowering onset and syrphid emergence. Snow melt and degree‐days were the best predictors of the end of flowering, whereas degree‐days and precipitation best predicted the end of the syrphid period. Flowering advanced at a faster rate than syrphids in response to both advancing snow melt and increasing temperature. Different rates of phenological advancements resulted in more days of temporal overlap between the flower–syrphid community in years of early snow melt because of extended activity periods. Phenological synchrony at the community level is therefore likely to be maintained for some time, even under advancing snow melt conditions that are evident over longer term records at our site. These results show that interacting taxa may respond to different phenological cues and to the same cues at different rates but still maintain phenological synchrony over a range of abiotic conditions. However, our results also indicate that some individual plant species may overlap with the syrphid community for fewer days under continued climate change. This highlights the role of interannual variation in these flower–syrphid interactions and shows that species‐level responses can differ from community‐level responses in nonintuitive ways.